The potential diagnostic yield of whole exome sequencing in pregnancies complicated by fetal ultrasound anomalies. (28th December 2020) - Diderich, Karin E. M.; Romijn, Kathleen; Joosten, Marieke; Govaerts, Lutgarde C. P.; Polak, Marike; Bruggenwirth, Hennie T.; Wilke, Martina; van Slegtenhorst, Marjon A.; van Bever, Yolande; Brooks, Alice S.; Mancini, Grazia M. S.; van de Laar, Ingrid M. B. H.; et al.
Abstract: Introduction: The aim of this retrospective cohort study was to determine the potential diagnostic yield of prenatal whole exome sequencing in fetuses with structural anomalies on expert ultrasound scans and normal chromosomal microarray results. Material and methods: In the period 2013‐2016, 391 pregnant women with fetal ultrasound anomalies who received normal chromosomal microarray results, were referred for additional genetic counseling and opted for additional molecular testing pre‐ and/or postnatally. Most of the couples received only a targeted molecular test and in 159 cases (40.7%) whole exome sequencing (broad gene panels or open exome) was performed. The results of these molecular tests were evaluated retrospectively, regardless of the time of the genetic diagnosis (prenatal or postnatal). Results: In 76 of 391 fetuses (19.4%, 95% CI 15.8%‐23.6%) molecular testing provided a genetic diagnosis with identification of (likely) pathogenic variants. In the majority of cases (91.1%, 73/76) the (likely) pathogenic variant would be detected by prenatal whole exome sequencing analysis. Conclusions: Our retrospective cohort study shows that prenatal whole exome sequencing, if offered by a clinical geneticist, in addition to chromosomal microarray, would notably increase the diagnostic yield in fetuses with ultrasound anomalies and would allow early diagnosis of a genetic disorder irrespective of the (incomplete) fetal phenotype.